On the essentialism of places: Between conservative and progressive meanings. (October 2019) - Lewicka, Maria; Rowiński, Kamil; Iwańczak, Bartłomiej; Bałaj, Bibianna; Kula, Agnieszka Maria; Oleksy, Tomasz; Prusik, Monika; Toruńczyk-Ruiz, Sabina; Wnuk, Anna
Abstract: Psychological essentialism is a widely studied concept within the social sciences, including the field of psychology. However, this concept has not been empirically explored when applied to perception of places. In this paper, we show that the essentialism vs. anti-essentialism philosophical controversy underlies the discussion carried out in human geography over what constitutes a place, understood as a meaningful location. In a series of three studies, we tested: (a) which places that conform to either essentialist or anti-essentialist criteria are judged by people as more meaningful and are preferred as living places, (b) what the structure of perceived place essentialism is, and (c) whether there exist affective markers of perceived place essentialism (emotions triggered by the essentialist vs. anti-essentialist features of places). In all three studies, pictures of respective locations were used. The studies showed that the places which conform to essentialist criteria were perceived to be more meaningful and were preferred to the anti-essentialist places. A two-dimensional essentialism vs. anti-essentialism structure described the perceived places the best. Affective reactions ordered along the dimensions of valence and arousal were systematically correlated to the perceived essentialism vs. anti-essentialism. The results confirm the claims made by cognitive psychologists that humans are psychological essentialists. The findings may contribute to the rising interest in the essentialism of artifacts. Highlights: Essentialist places were perceived as more meaningful and were preferred to anti-essentialist places. The valence x arousal core affect was systematically correlated with place essentialism/anti-essentialism. The findings contribute to the discussion on the essentialism of artifacts.